Effect of farming methods on rivers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Perennial rivers are a source of livelihood to many rural people in the sub-humid tropics, where villages are often strategically situated along the river banks. The rivers provide water for irrigation and income from fishing, as well as a means of...